El Aprendizaje y la Memoria - Trelles, Luis (1993)
The hippocampus is the brain region where takes place the biological mechanisms of explicit memory. Explicit memory refers to the type of learning restorable through language, such as biographic facts or academic knowledge. Recent experimental findings have enlarged our comprehension about hippocampal function. Based on them, the author suggests a hypothesis about the bíological basis of learning.